The Impact of Upper Abdominal Surgery Regarding the Outcome of Patients with Advanced Ovarian Cancer - Pietschmann, Maximilian; Jaeger, Anna; Reuter, Susanne; Schmalfeldt, Barbara (Geburtshilfe und Frauenheilkunde, 2024)
Residual tumor after cytoreductive surgery is the most important prognostic parameter for the outcome of patients with advanced ovarian cancer (5-year survival rate FIGO III 39%, FIGO IV 20%). As more than half of the patients suffer from upper abdominal tumor burden, surgery in this area is inevitable in order to achieve adequate cytoreduction. Our analysis focuses on the impact of upper abdominal interventions (UAI) regarding residual tumor and prognosis (OS, PFS).A total of n = 261 patients with advanced primary ovarian cancer stage FIGO III and IV and radical cytoreductive surgery at the Gynecologic Cancer Center Hamburg-Eppendorf between 2014 and 2019 were analyzed in a retrospective study design and divided into two groups: one with UAI (n = 160) and one without UAI (n = 101).Patients with UAI showed significantly more often a residual tumor of less than 1 cm (R1) than patients without UAI and had a significantly longer OS (59 vs. 45 months [p = 0.041]). Deperitonealization of the diaphragm was the most common (144/160) and prognostically most relevant procedure for UAI. Especially the subgroup with FIGO IIIC stage seemed to benefit most from UAI. However, in multivariate analysis residual tumor burden was the strongest prognostic parameter for survival, followed by FIGO stage and UAI. Mortality was low within in the UAI group (0.6%).UAI is an essential part of cytoreductive surgery in advanced ovarian cancer patients with tumor spread into the upper abdomen as it significantly prolongs survival. The procedure appears to be safe with low mortality. Achieving R1 rather than R2 due to radical surgery combined with UAI should be preferred compared to the early termination of the operation, as this has a significant impact on the prognosis of the patients.
Keywords: cancer registry; ovarian cancer; ovary